2007
DOI: 10.1038/sj.npp.1301642
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of AMPA Receptor Endocytosis Impairs the Extinction, but not Acquisition of Learned Fear

Abstract: Synaptic plasticity in the form of long-term potentiation (LTP) plays a critical role in the formation of a Pavlovian fear association. However, the role that synaptic plasticity plays in the suppression of a learned fear response remains to be clarified. Here, we assessed the role that long-term depression (LTD) plays in the acquisition, expression, and extinction of a conditioned fear response. We report that blockade of LTD with a GluR2-derived peptide (Tat-GluR2 3Y ; 1.5 mmol/kg, i.v.) that blocks regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
135
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(146 citation statements)
references
References 70 publications
8
135
0
Order By: Relevance
“…If deprivation of sleep is more related to the function of the mushroom bodies ( Joiner et al 2006) than consolidation of memory after such configural forms as extinction, then learning may be more strongly affected. Furthermore, several studies have shown that acquisition learning and extinction learning are different in many aspects (Bouton et al 1993;Myers and Davis 2002;Gottfried and Dolan 2004;Eisenhardt and Menzel 2007), and conditions have been reported that interfere with consolidation of extinction memory while sparing other forms of memory (Silvestri 2005;Fu et al 2007;Dalton et al 2008). It is thus possible that sleep deprivation affects only extinction learning, a question that needs to be addressed in further experiments.…”
Section: Discussionmentioning
confidence: 96%
“…If deprivation of sleep is more related to the function of the mushroom bodies ( Joiner et al 2006) than consolidation of memory after such configural forms as extinction, then learning may be more strongly affected. Furthermore, several studies have shown that acquisition learning and extinction learning are different in many aspects (Bouton et al 1993;Myers and Davis 2002;Gottfried and Dolan 2004;Eisenhardt and Menzel 2007), and conditions have been reported that interfere with consolidation of extinction memory while sparing other forms of memory (Silvestri 2005;Fu et al 2007;Dalton et al 2008). It is thus possible that sleep deprivation affects only extinction learning, a question that needs to be addressed in further experiments.…”
Section: Discussionmentioning
confidence: 96%
“…targets have also been implicated in memory destabilization during reconsolidation Hong et al 2013) and in extinction (Kim et al 2007;Dalton et al 2008;Lee et al 2008), suggesting that this memory labilization system might mediate both the labilization component of reconsolidation and the within-session component of memory extinction.…”
Section: Discussionmentioning
confidence: 99%
“…Fear extinction recruits the infralimbic cortex to exert inhibitory influence on the medial subnuclei of the central amygdala (CeM) via the basal amygdala (BA) and amygdala-intercalated neurons (Maren and Quirk, 2004;Haubensak et al, 2010;Pape and Pare, 2010;Amir et al, 2011). Extinction also induces depotentiation at LA input synapses (Kim et al, 2007;Dalton et al, 2008;Hong et al, 2009) and enhances local inhibition (Chhatwal et al, 2005;Lin et al, 2009), all leading to decreased fear expression. Interestingly, NMDA receptor blockers infused into the LA impair both fear conditioning and extinction, suggesting that neuronal plasticity in the LA is crucial for both events (Miserendino et al, 1990;Falls et al, 1992;Sotres-Bayon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%